Optimizing Adolescent Reproductive Health: A Comprehensive Educational Program at Al-Hasani Islamic Boarding School in Pontianak - Masdah, Siti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Teenagers are those in the age range of 10-19 years. Adolescents are also a very vulnerable group that requires special attention to reproductive health. Reproductive health education services need to be carried out at Islamic boarding schools because students cannot consult with health workers directly due to the unavailability of health facilities at Islamic boarding schools; students are prohibited from bringing mobile phones, and they rarely meet with parents. Those who have good knowledge regarding reproductive health are 3.4 times more likely to behave appropriately in caring for their reproductive organs. Knowledge can raise their awareness regarding the importance of correct reproductive organ care. The purpose of this activity is to increase the knowledge of Islamic boarding school youth regarding reproductive health and to be able to apply it in their own lives. The community service method is carried out for students at the Al-Hasani Islamic Boarding School, Pontianak city. The delivery method uses the lecture method with material regarding adolescent reproductive health. The implementation process also uses pretests and posttests to see the success of education in increasing student knowledge. The results of the service found that there was an increase in knowledge of students after being given adolescent reproductive health education. For male students, there was an increase in knowledge from less to sufficient, while for female students there was an increase in knowledge from less to good. Based on the study, it can be concluded that Islamic boarding school students still consider reproductive health education a taboo. There needs to be a separation location of reproductive health education for male and female students so that they are more flexible to ask questions to the presenters regarding reproductive health issues